Konsep Komunitas dalam Pemikiran dan Dakwah Said Nursi - Amin, Edi (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2015)
This paper discusses the thoughts and activities of Said Nursi Dakwah movement, especially on the concept of community. To collect the data this study uses text analytics to the works of Nursi, observation and interviews. It is ex–pected that by used such a research, the meanings of verbal and non-verbal communication can be interpreted to obtain a more complete picture of the Nur activities of Dakwah so that the discussion does not get stuck on merely historical empirical approach. The authors conclude that the Nursi Dakwah movement is a non-political movement that em–phasizes a commitment to the values of the universality of Islam. In addition, the concept of community in the Nursi thought empowers the Communitarian theory established by Hamid Mowlana and Wilson (1990), and Majid Tehranian (1989).